(untitled) (Research, Society and Development, 2020)
Within a fast-paced consumer society many products are targeted to social subjects, however not all are acquired by them. Consumption relations are not free of crossings that change, direct or redirect themselves. One of these crossings is the identity. This essay proposes a reflection on the cultural dynamics between identity and consumption from the perspectives of Cultural Theory, whose main name is Stuart Hall, and the Philosophy of Difference proposed by the philosophers Deleuze and Guattari; understand how the interference between them occurs at the subjective level and, thus, contribute to the debate about the possibilities and forms of consumption in the contemporary moment of hypermodernity and constant search for happiness through consumption. By the intersections between the theories and by the perspective of identification and singularization, we conclude that both point to subcultural consumption as a hybrid activity that, even though it is systematically reintegrated into the rhizome, also constitutes a break with it. Finally, subcultural consumption is an essential element in the subsistence dynamics of cultural groups, such as the case of the Gothic subculture, analyzed in this essay.